Pengaruh Kesadaran Wajib Pajak, Sanksi Perpajakan, Dan Pelayanan Fiskus Terhadap Kepatuhan Wajib Pajak Orang Pribadi (Studi Empiris Kabupaten Klaten) - Indriati, Henny; Pardanawati, Sri Laksmi; Utami, Wikan Budi; Wahyuningtyas, Nofi (ITB AAS INDONESIA, 2022)
The purpose of this study was to determine the awareness of taxpayers, tax sanctions, and tax service services on individual taxpayer compliance. This type of research is classified as quantitative research. The population in this study is an individual taxpayer in Klaten Regency. Sample selection using incidental sampling technique, with a total sample of 100 respondents. The type of data used is subjective data, and the data source used is primary data. The data collection method used is by using a questionnaire in the form of closed questions. The results of the study show that 1) taxpayer awareness, tax sanctions, and tax service services have a simultaneous effect on individual taxpayer compliance, 2) taxpayer awareness has a significant effect on individual taxpayer compliance, 3) tax sanctions have no effect on taxpayer compliance. individual tax, 4) tax service services have a significant effect on individual taxpayer compliance. Keywords: Taxpayer compliance, taxpayer awareness, tax sanctions, and tax service.